2017
DOI: 10.4142/jvs.2017.18.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in antioxidant function and cell apoptosis in duck spleen exposed to molybdenum and/or cadmium

Abstract: To investigate the effects of molybdenum (Mo) and/or cadmium (Cd) on antioxidant function and the apoptosis-related genes in duck spleens. Sixty healthy 11-day-old ducks were randomly divided into six groups of 10 ducks (control, low Mo group, high Mo, Cd, low Mo + Cd, and high Mo + Cd groups). All were fed a basal diet containing low or high dietary doses of Mo and/or Cd. Relative spleen weight, antioxidant indices, apoptosis-related gene mRNA expression levels, and ultrastructural changes were evaluated afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
4
6
0
Order By: Relevance
“…Excess Mo is mainly related to occupational activities or contaminated nutrients, whose consequences are not well characterized. It has been reported in ducks that spleen Mo accumulation decreases antioxidant capacity, favors cell apoptosis, and increases heat shock proteins and TNF-a in spleen (38,39). Similar data have been found in chickens fed with a high-Mo diet (40).…”
Section: Discussionsupporting
confidence: 79%
“…Excess Mo is mainly related to occupational activities or contaminated nutrients, whose consequences are not well characterized. It has been reported in ducks that spleen Mo accumulation decreases antioxidant capacity, favors cell apoptosis, and increases heat shock proteins and TNF-a in spleen (38,39). Similar data have been found in chickens fed with a high-Mo diet (40).…”
Section: Discussionsupporting
confidence: 79%
“…Molybdenum is a critical component of several enzymes, including sulfite oxidase, XOD, and aldehyde oxidase [36]. High dietary MO levels decreased serum XOD activity in agreement with the result of Zhang et al [37]. Moreover, in this study, high dietary MO levels resulted in decreased activities of antioxidant enzymes (T-AOC, XOD, GSH-ST) and GSH concentration while MDA levels were increased.…”
Section: Discussionsupporting
confidence: 89%
“…Studies in rabbits have shown that high MO accumulation generates free radical processes or reactive intermediates, resulting in the alteration of MDA and GSH-Px levels [44,45]. In ducks exposed to high levels of MO, an increase in MDA levels and a decrease in XOD and CAT activities in serum and spleen tissue has also been observed [28,37]. Therefore, the toxic effect of exposure to high MO levels can result in oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 11 ] found that Pb caused ultrastructural changes and apoptosis in rat proximal tubular cells. Zhang et al [ 47 ] found that molybdenum and Cd changed ultrastructural structure and induced apoptosis in duck spleens. Nickel chloride decreased Bcl-2 mRNA expression, increased Bax, Cyt c, and Caspase-3 mRNA expression, and induced apoptosis via mitochondrial pathway in chicken bursa of Fabricius [ 48 ].…”
Section: Discussionmentioning
confidence: 99%